Leadership and competency on organizational performance - Raduan Che Rose; Naresh Kumar; Syafiq Alfonse Abdullah (2006)
The main objective of this study was to examine the relationship between leadership characteristics and managerial competency of the CEO to organizational performance. The findings did indicate that the relationship did exist, with leadership characteristics contributed significantly more to organizational performance than managerial competency. The findings also indicated the leadership characteristics of persistence accounting more for organizational performance than any of the other leadership characteristics or managerial competency variables, although the managerial competency grouping of results driven showed a significant relationship with organizational performance. With regard to the demographic profile of the CEOs, the educational level did indicate a significant relationship with organizational performance. Similarly the size of the business organization also did indicate a significant relationship with organizational performance